2011
DOI: 10.1007/978-3-642-21799-9_48
|View full text |Cite
|
Sign up to set email alerts
|

Using Physiological Parameters to Evaluate Operator’s Workload in Manual Controlled Rendezvous and Docking (RVD)

Abstract: How to train the astronauts for complicated operation in spaceflight such as manually controlled rendezvous and docking (RVD) is a common and important question. In this paper, two training methods named Routine method and Confusing method were proposed from astronaut training experience. Two-factor experiment was conducted. The factors are training method and operation difficulty level. Sixteen male subjects participated in this experiment. Eight participants were trained with Routine method and the other eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Dussault et al, (2005) also observed HR was lower for experts rather than novices when carrying out the same task. However, significant differences were also observed in HR and HRV between different training methods (Wu et al, 2011) which again highlights the difficulties of comparing studies that use different experience levels.…”
Section: Rmssd Msmentioning
confidence: 97%
See 3 more Smart Citations
“…Dussault et al, (2005) also observed HR was lower for experts rather than novices when carrying out the same task. However, significant differences were also observed in HR and HRV between different training methods (Wu et al, 2011) which again highlights the difficulties of comparing studies that use different experience levels.…”
Section: Rmssd Msmentioning
confidence: 97%
“…The experimental, domain-free and simulated fixed-wing operations are more represented in the sample of literature reviewed (Table 4). Braby et al, 1993;Delaney and Brodie 2000;Durantin et al, 2014;Hart and Hauser 1987;Lahtinen et al, 2007;Lee and Liu 2003;Lehrer et al, 2010;Luque-Casado et al, 2016;Mansikka et al, 2016a;Mansikka et al, 2016b;Miyake 2001;Myrtek et al, 1994;Nickel and Nachreiner 2003;Sauer et al, 2013;Schellekens et al, 2000;Tattersall and Hockey 1995;Tripathi et al, 2003)   (Backs 1994;Wu et al, ( Holland and Tarlow, 1972;Recarte and Nunes, 2003;Reiner and Gelfeld, 2014)     (Brookings et al, 1996;Fairclough et al, 2005;Fournier et al, 1999;Sirevaag et al, 1993;Wilson and Russell 2003;Wilson 1993)   (Finsen et al, 2001;Hjortskov et al, 2004)   (Dussault et al, 2004;Dussault et al, 2005;Hsu et al, (Braby et al, 1993;Svensson and Wilson 2009) 2…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…1 Wearable sensor technology developed by CSEM SA and used in this study decreasing the gap between the laboratory and the eventual application (Guzik and Malik 2016). We capture cardiac measures that have been shown to differentiate taskloads (De Rivecourt et al 2008;Fairclough et al 2005;Splawn and Miller 2013) and respiration rates (Backs et al 2000;Brookings et al 1996;Wu et al 2011;Yao et al 2008).…”
Section: Introductionmentioning
confidence: 99%